Role of the left coronary artery geometry configuration in atherosusceptibility: CFD simulations considering sPTT model for blood. Issue 13 (3rd October 2021) - Miranda, E.; Sousa, L.C.; António, C.C.; Castro, C.F.; Pinto, S.I.S.
Abstract: The achievement of clinically viable methodologies to simulate the hemodynamics in patient-specific coronary arteries is still a major challenge. Therefore, the novelty of this work is attained by the introduction of the viscoelastic property of blood in the numerical simulations, to study the role of the left coronary artery (LCA) geometry configuration in the atherosusceptibility. Apparently healthy patients were used and four different methodologies were tested. The methodology giving the most accurate results at the same time of having the lowest computational time is the one considering the viscoelastic property of blood and computational fluid dynamics. A Pearson correlation analysis was used to highlight relationships between geometric configuration and hemodynamic descriptors based on the simulated wall shear stress (WSS). The left main stem (LMS) has the greatest atherosusceptibility followed by the left anterior descending artery (LAD) since the relative residence time (RRT) average values are 3.81 and 3.70 Pa −1, respectively. The geometric parameters with relevant contribution to directional flow change are the cross-sectional areas, especially the one of LMS segment (ALMS ), and the curvature of LMS segment. For LMS and LAD segments, when ALMS increases, blood flow disturbance (r = 0.81 in LMS and r = 0.74 in LAD) and atherosusceptibility (r = 0.84 in LMS and r = 0.85 in LAD) increases. When the LMS curvature decreases, the WSS magnitude (r = 0.80 in LMS and r = 0.83 in LAD) decreases, and disturbance (r=-0.80 in LMS and r=-0.91 in LAD) and atherosusceptibility (r=-0.74 in LMS and r=-0.74 in LAD) increases.